2022
DOI: 10.1021/acs.estlett.2c00484
|View full text |Cite
|
Sign up to set email alerts
|

p-Phenylenediamine-Derived Quinones as New Contributors to the Oxidative Potential of Fine Particulate Matter

Abstract: Atmospheric fine particulate matter (PM 2.5 ) has been linked to multiple adverse outcomes, where redox-active species-induced oxidative stress is recognized as an important driver of its biotoxicity. Previous studies have proven that the oxidative potential (OP) is a relevant metric for specific acute PM 2.5 health effects and is associated with various toxicants, especially organic quinones. However, discrepancies between OP induced by the known components and its total levels caused by PM 2.5 remain. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Notably, in addition to the commonly detected 6PPDQ, four other environmental PPDQs were frequently detected in these rubber products, especially the detections of DPPDQ and DTPDQ in crumb rubber at similar concentrations to 6PPDQ. These PPDQ detections again indicate that quinone TP formation may occur for many PPD antioxidants, producing PPDQs with as-yet unknown toxicity characteristics. ,, In addition to the quinone products, other interesting TPs of 6PPD were detected, including the bioactive stimulant 1,3-DMBA and the potentially carcinogenic nitroso-compound 4s DPA.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Notably, in addition to the commonly detected 6PPDQ, four other environmental PPDQs were frequently detected in these rubber products, especially the detections of DPPDQ and DTPDQ in crumb rubber at similar concentrations to 6PPDQ. These PPDQ detections again indicate that quinone TP formation may occur for many PPD antioxidants, producing PPDQs with as-yet unknown toxicity characteristics. ,, In addition to the quinone products, other interesting TPs of 6PPD were detected, including the bioactive stimulant 1,3-DMBA and the potentially carcinogenic nitroso-compound 4s DPA.…”
Section: Resultsmentioning
confidence: 76%
“…These PPDQ detections again indicate that quinone TP formation may occur for many PPD antioxidants, producing PPDQs with as-yet unknown toxicity characteristics. 17,18,21 In addition to the quinone products, other interesting TPs of 6PPD were detected, including the bioactive stimulant 1,3-DMBA and the potentially carcinogenic nitroso-compound 4s DPA.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of the acute lethality of 6PPD-Q to salmonids are still unclear, although the disruption of the blood–brain barrier, mitochondrial dysfunction, and oxidation were indicated as the key events that are responsible for the high toxicity of 6PPD-Q. ,, More research is needed to gain a comprehensive understanding of the mechanism by which 6PPD-Q can induce acute lethality to some salmonid species and to elucidate the causes of large interspecies differences in sensitivity. This study demonstrates the 6PPD-Q concentrations in brain and gill of insensitive salmonid species without apparent symptoms might be higher than those in the sensitive species S. leucomaenis pluvius showing mortality symptoms, which indicates that species sensitivity differences may be somewhat driven by toxicodynamic factors.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, 6PPD and 6PPD-Q have been found in a variety of environmental matrices, including atmospheric particles, , indoor dust, ,, road dust, , playground dust, roadside soil, runoff water, ,, and surface water. In most cases, 6PPD and 6PPD-Q coexisted in these environmental matrices at comparable concentrations. For instance, Zhang et al demonstrated ubiquitous distributions of 6PPD and 6PPD-Q in fine particulate matters (PM 2.5 ) from six Chinese cities, and the atmospheric concentrations of 6PPD (median 0.9–8.4 pg/m 3 ) were found to be similar to those of 6PPD-Q (median 1.7–6.7 pg/m 3 ) .…”
Section: Introductionmentioning
confidence: 99%